Infliximab for chronic cutaneous sarcoidosis: a subset analysis from a double-blind randomized clinical trial - Baughman, Robert P.; Judson, Marc A.; Lower, Elyse E.; Drent, Marjolein; Costabel, Ulrich; Flavin, Susan; Lo, Kim Hung; Barnathan, Elliot S.; Sarcoidosis Investigators, on behalf of the (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Limited evidence exists demonstrating an effective treatment for chronic cutaneous sarcoidosis. Objective: To determine infliximab’s effectiveness in sarcoidosis. Methods: We conducted a subset analysis from a randomized, double-blind, placebo-controlled trial for chronic pulmonary sarcoidosis to determine infliximab’s effectiveness. Patients with chronic cutaneous sarcoidosis received infliximab (3 or 5 mg/kg) or placebo over 24 weeks. Of 138 patients, the subset analysis evaluated 17 patients with chronic facial and another 9 patients with nonfacial skin involvement. The SASI evaluated lesions for degree of erythema, desquamation, induration, and percentage of area involved. Facial and nonfacial lesions were scored in a blinded manner. Results: Among 5 placebo-treated and 12 infliximab-treated patients, an improvement was observed with infliximab versus placebo in change from baseline to weeks 12 and 24 in desquamation (P<0.005) and induration (P<0.01) at week 24. Erythema, percentage of area involved and the evaluation of paired photographs did not reveal significant differences. Limitations: Sample size; more extensive disease in placebo patients; chronic therapy upon enrollment; lung as primary organ of sarcoidosis involvement; limited investigator experience with SASI. Conclusions: Infliximab appears to be a beneficial treatment for chronic cutaneous sarcoidosis. The SASI scoring system demonstrated significant improvement versus placebo in lesion desquamation and induration. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 289-295)